Characteristics of Liquid Egg White with Addition of Forest Bee Honey During Cold Storage - Saputri, K. W.; Nurliyani; Widodo (Tropical Animal Science Journal, 2024)
Eggs were perishable foodstuffs during distribution to consumers. Hence, appropriate egg handling and preservation methods were needed and could be applied to farmers and the egg processing industry. This research aimed to evaluate the effect of adding forest bee honey (Apis dorsata) on the physicochemical and microbiological qualities of liquid egg whites at storage temperature of 4 °C. The treatments consisted of three levels of honey (0%, 5%, and 10%) with storage durations of 0, 1, 2, 3, 4, 5, 6, 7, and 8 weeks. The variables analyzed include physical properties (foam capacity and foam stability), chemical properties (S-ovalbumin and protein profile on SDS-PAGE), and total plate count (TPC). The results revealed that the interaction of storage time and the addition of honey has a significant effect (p<0.05) on foam capacity, foam stability, S-ovalbumin, and TPC. Egg whites with 10% honey had higher foam capacity and foam stability, but lower S-ovalbumin content and the number of microbes after eight weeks compared to egg whites with 0% honey and 5% honey. In conclusion, the addition of 10% forest bee honey could maintain physicochemical qualities and extend the shelf life of liquid egg white during 8 weeks of cold storage.